International Arbitration to Resolve International Commercial Disputes under the Provisions of Private International Law (International Journal of Financial, Administrative and Economic Sciences, 2025)
Arbitration is one of the oldest institutions entrusted with the task of resolving and settling disputes. It has accompanied humankind since ancient times and evolved with the development of international trade. It has become an inherent and deeply ingrained custom in people's psyches. They believe it is a function of the judiciary and justice, and a means of resolving disputes. Arbitration is considered one of the most important means of resolving contractual disputes in the field of commercial and investment relations, due to its many characteristics and features that have enticed many comparative legal systems to resort to it. It is characterized by fairness, confidentiality, speed, economy, and the avoidance of routine and traditional procedures in resolving all disputes. These qualities make it the primary guarantee for investors, dispelling their fears of the specter of the host country's national authority and the risks of its use of the concept of sovereignty to initiate procedures that undermine the investor's gains, assets, and contracts concluded with national entities. Arbitration is a type of private judiciary, in which the disputing parties freely choose it as a means of resolving their dispute, selecting the arbitrators they represent, the procedures to be followed, and sometimes the law applicable to it.
Keywords: International Arbitration; International Commercial Disputes; Private International Law